2022
DOI: 10.3390/app12073599
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Resource Potential of Baltic Sea Macroalgae

Abstract: The excess biomass of drifting algae and their casting to the Baltic Sea coast imposes a significant environmental burden. The analysis of beach-cast algae showed that the dominant species are macroalgae Ulva sp., Furcellaria lumbricalis, Cladophora sp., and Polysiphonia fucoides. The biomass of Furcellaria and Polysiphonia algae, containing 25.6% and 19.98% sugars, respectively, has the greatest resource potential in terms of obtaining carbohydrates. Fucose, glucose, and galactose were found to be the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 84 publications
0
12
0
Order By: Relevance
“…According to Li et al ( 86 ), LAB fermentation has a significant impact on the phenolic profile, as well as on antioxidant activity, because during the process, various phenolic acids could be excreted to the fermentable matrix ( 86 ). It was reported that Furcellaria extracts, in comparison with Cladophora and Ulva sp ., had the highest antioxidant activity of all the macroalgae alcoholic extracts tested ( 87 ). It has also been shown that the ethanolic extract of green and red seaweeds exhibit a high scavenging activity and a higher DPPH • of brown and green seaweeds in comparison with red ( 83 , 88 90 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Li et al ( 86 ), LAB fermentation has a significant impact on the phenolic profile, as well as on antioxidant activity, because during the process, various phenolic acids could be excreted to the fermentable matrix ( 86 ). It was reported that Furcellaria extracts, in comparison with Cladophora and Ulva sp ., had the highest antioxidant activity of all the macroalgae alcoholic extracts tested ( 87 ). It has also been shown that the ethanolic extract of green and red seaweeds exhibit a high scavenging activity and a higher DPPH • of brown and green seaweeds in comparison with red ( 83 , 88 90 ).…”
Section: Resultsmentioning
confidence: 99%
“…All members of this order are able to produce methane from CO 2 and H 2 . In many species, formate and secondary alcohols are used as alternative electron donors [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Not only does the processing of drifting macroalgae into value-added products solve the climatic and environmental problems of coastal zone cleaning, but it also has a significant economic impact, including a multiplicative nature, at least by increasing its tourist attractiveness [10] . The concept of “zero-waste production” is a key concept in today's biofuel industry.…”
Section: Introductionmentioning
confidence: 99%